Naturally occurring auxotrophs of Campylobacter jejuni and Campylobacter coli. - Tenover, F C (1987)
The nutritional requirements for 439 Campylobacter jejuni isolates and 46 Campylobacter coli isolates were determined by using a previously described chemically defined medium, campylobacter defined medium. With this medium, 45% of both human and nonhuman C. jejuni isolates demonstrated auxotrophic requirements. None of the 46 C. coli isolates studied demonstrated requirements for amino acids on campylobacter defined medium. The most common auxotrophic requirement among C. jejuni isolates was for methionine, which was present as a single requirement or in combination with other markers in 21% of human and 28% of nonhuman isolates. There was no correlation between plasmid carriage and auxotype, and a comparison of the Lior serotypes of 472 of the strains showed a correlation only between proline auxotrophs and Lior serotype 11 for strains isolated in the Seattle-King County region.